FTIR SPECTRUM ANALYSIS OF SILICON DOPED WITH ERBIUM - Sharifa B; Utamuradova, Jonibek J. Khamdamov, Bekzod Sh. Alikulov; Khojakbar S. Daliyev (Research Focus International Scientific Journal, 2025)
Semiconductor materials based silicon are a key component of modern microelectronics and optoelectronics. In particular, when Erbium (Er) is introduced into the crystal lattice, a number of important structural changes occur in the silicon structure. In silicon, such changes are particularly well detected by infrared (FTIR) spectroscopy, since this method can accurately record the vibrational modes of bonds such as Si–O–Si, Er–O, Si–C, etc. The formation of new phases in the structure, the degree of oxidation, and the concentration of optically active oxygen are estimated by the location, intensity, and width of the peaks obtained using FTIR. The most important changes were noted around the Si–O–Si assymmetric stretching vibration (νₐs) line. While this peak was detected at 1099 cm-¹ in the sample with erbium atoms introduced, in the original sample it shifted to 1109 cm-¹, its intensity also decreased, and the line broadened. These changes are explained by the formation of an oxygen-enriched but highly disordered amorphous SiOₓ layer during thermal treatment. As a result, the angle in the Si–O–Si bonds widens, the bond length increases slightly, which leads to a decrease in the vibrational frequency, along with a decrease in bond elasticity. The broadening of the peak indicates an increase in the angle and bond length distribution in the structure.